An investigation of language learning strategies among Form 6 students / Illani Muhamed Kamil - Muhamed Kamil, Illani (2014)
This research investigates the use of language learning strategies (LLS) among 130 form 6 students from SMK Sungai Kapar Indah, Kapar. By using Oxford’s (1990) Strategy Inventory for Language Learners (SILL) as the method, this study also seeks to find out the language learning strategies particularly English, according to the students’ gender and proficiency level. The students’ proficiency level is measured according to their Malaysian University English Test (MUET) score. The 3 research questions in this study are answered by using Statistical Package for the Social Science (SPSS). To find what are the LLS employed by the students, descriptive analysis was used to get the mean and then they were ranked accordingly. It was found that all LLS fell within the medium usage range. Metacognitkve was at the first rank followed by social, compensatory, memory, affective and lastly cognitive strategy. The second objective of carrying out this study is to investigate the differences among learners in strategy use and their gender, results of a oneway analysis of variance (ANOVA) showed that there was a significant difference in the usage of affective and social strategies between male and female students. Male used significantly more affective strategy and social strategy than female students. Lastly, in order to know the differences among learners in their strategy use and their proficiency level, ANOVA again was used to find the significant difference and Fisher’s LSD post-hoc test was utilized to find differences across the bands among each LLS. It is found that there was no statistically significant difference between the groups of students and the usage of metacognitive, compensatory and social strategies were the highest among Band 4 students. However, additional result obtained by comparing difference in strategies usage revealed that Band 1 scorers use more cognitive and compensatory strategies than Band 3 scorers. Based on the findings, it can be said that the students in SMK Sungai Kapar Indah are not aware of which learning strategies to employ when they are learning English. This can be seen from the overall medium usage of learning strategies among the participants. It is imperative for the students to be made aware of how to employ these strategies as this might be useful for them to get higher and better bands in MUET as MUET is a pre-requirement for the students to enter universities. The implication of the study is that, students who have different bands in MUET should be made aware employing LLS to improve their English learning.